Just around the corner - McMullan, W. Ed
Following his two previous papers regarding this entrepreneurial activities in setting up a speciality chemical company and its subsequent development, Professor McMullan brings us up to date in an eye-opening manner on the most recent financial, commercial, and personal problems encountered.